Creutzfeldt-Jakob Disease Involvement of Rolandic Cortex: A Quantitative Apparent Diffusion Coefficient Evaluation - Lin, Y.-R.; Young, G.S.; Chen, N.-K.; Dillon, W.P.; Wong, S. (American Journal of Neuroradiology, 2006)
BACKGROUND: Previous reports have suggested that abnormally reduced water diffusivity and T2 prolongation involving cerebral gray matter in patients with early sporadic Creutzfeldt-Jakob disease (sCJD) involves all areas of neocortex with similar frequency, except for primary sensorimotor cortex (Rolandic cortex) and visual cortex. Rolandic cortex often appears to be spared even in the presence of extensive surrounding neocortical signal intensity abnormality in adjacent frontal and parietal gray matter. A quantitative apparent diffusion coefficient (ADC) analysis was designed to investigate whether this unusual pattern results from pathophysiologic sparing of Rolandic cortex or from reduced conspicuity of signal intensity abnormality on MR imaging echo-planar diffusion-weighted images (epiDWI) related to unknown underlying features of Rolandic cortex.METHODS: ADC maps were derived from epiDWI of 6 patients with sCJD and 8 control patients. Bilateral regions of interest were manually selected in precentral gyri, superior frontal gyri, postcentral gyri, supramarginal gyri, thalamus, putamen, and caudate nuclei. ADC and relative ADC (rADC) values were calculated for each region of interest.RESULTS: Patients with CJD had significantly lower ADC values than control patients in all areas (P ≤ 0.05). The trend toward decreased ADC values in the deep nuclei correlates well with previously published reports. rADC were not significantly different between CJD and control groups in any area (P > 0.25 in all cases).CONCLUSION: Quantitative ADC measurements in patients with early sCJD demonstrate a similar degree of reduced water diffusivity in the primary somatosensory cortex as in other neocortical areas, despite the normal appearance of these areas on visual inspection of epiDWI.